Low-Voltage Current-Sensing CMOS Interface Circuit for Piezo-Resistive Pressure Sensor - Apinunt Thanachayanont; Suttisak Sangtong (My University, 2007)
A new low-voltage CMOS interface circuit with digital output for piezo-resistive transducer is proposed.An input current sensing configuration is used to detect change in piezo-resistance due to applied pressure and to allow lowvoltage circuit operation.A simple 1-bit first-order deltasigma modulator is used to produce an output digital bitstream.The proposed interface circuit is realized in a 0.35 µm CMOS technology and draws less than 200 μA from a single 1.5 V power supply voltage.Simulation results show that the circuit can achieve an equivalent output resolution of 9.67 bits with less than 0.23% nonlinearity error.
Keywords: Bitstream; Resistive touchscreen; Linearity; Diode-or circuit; Interface (matter); Advanced MEMS and NEMS Technologies